The Influence of Digital Literacy and Product Innovation on the Competitive Advantage of Modern Beverage Businesses - Kurniawan, Ivan; Wulan, Ni Ketut Arieshanti (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study focuses on local wisdom concerning Komodo dragons in Indonesia. Despite the global recognition of Komodo dragons as an endangered species, cultural values such as the "Putri Naga" narrative are diminishing among local communities. Preliminary surveys showed a drop in cultural literacy. Only 12% of local adolescents were familiar with the narrative. The objective of this study was to address this issue by designing an educational comic book that integrates biological data with local mythological stories. The present study employed a qualitative methodology, utilising a comprehensive approach to data collection. This approach entailed a literature review, expert interviews, field observations, and questionnaires to 64 respondents. The semi-realistic illustration style was chosen to suit the audience and the theory of visual communication. This approach has been found to be an effective means of conveying biological information, including the anatomy, behaviour and habitat of the Komodo dragon, whilst simultaneously introducing myths about the dragon. Furthermore, the incorporation of visual elements, including traditional woven fabric motifs, served to reinforce local identity. The culmination of the research endeavour was the publication of a comic book bearing the title "Eksplora: Jejak Orah." The narrative of this comic is structured around a fantasy storyline, interspersed with factual biology and mythical narratives concerning the Komodo Dragon. The study demonstrates that well-designed visual storytelling can function as an effective pedagogical tool. The implications of this phenomenon extend to the realm of intangible cultural heritage protection and the enhancement of ecological literacy among young individuals.